Cerebellar Direct Current Stimulation Enhances On-Line Motor Skill Acquisition through an Effect on Accuracy - Cantarero, Gabriela (J Neurosci, 2015)
The cerebellum is involved in the update of motor commands during error-dependent learning. Transcranial direct current stimulation (tDCS), a form of noninvasive brain stimulation, has been shown to increase cerebellar excitability and improve learning in motor adaptation tasks. Although cerebellar involvement has been clearly demonstrated in adaptation paradigms, a type of task that heavily relies on error-dependent motor learning mechanisms, its role during motor skill learning, a behavior that likely involves error-dependent as well as reinforcement and strategic mechanisms, is not completely understood. Here, in humans, we delivered cerebellar tDCS to modulate its activity during novel motor skill training over the course of 3 d and assessed gains during training (on-line effects), between days (off-line effects), and overall improvement. We found that excitatory anodal tDCS applied over the cerebellum increased skill learning relative to sham and cathodal tDCS specifically by increasing on-line rather than off-line learning. Moreover, the larger skill improvement in the anodal group was predominantly mediated by reductions in error rate rather than changes in movement time. These results have important implications for using cerebellar tDCS as an intervention to speed up motor skill acquisition and to improve motor skill accuracy, as well as to further our understanding of cerebellar function.